Thermodynamic analysis and optimization of a transcritical CO2 geothermal power generation system based on the cold energy utilization of LNG - Wang, Jianyong; Wang, Jiangfeng; Dai, Yiping; Zhao, Pan (Applied thermal engineering, 2014)
This paper investigates a transcritical CO2 cycle using geothermal resources to generate electricity. Liquefied natural gas (LNG) is employed as heat sink to drop the CO2 turbine back pressure sharply. The mathematical model of the transcritical CO2 geothermal power generation system is established for system simulations under steady-state conditions. A parametric analysis is conducted to evaluate the effect of several key thermodynamic parameters on system performance. Additionally, a multi-objective optimization using NSGA-II method is carried out to find the optimum performance of system from both thermodynamic and economic aspects. The results show that there is an optimal CO2 turbine inlet pressure that yields the maximum exergy efficiency. A higher CO2 turbine inlet temperature or a lower CO2 turbine back pressure brings about a higher exergy efficiency. In addition, an optimal CO2 turbine inlet pressure obtains the minimum required heat exchange area per net power output. The lower the CO2 turbine inlet temperature or the CO2 turbine back pressure is, the smaller the required heat exchange area per net power output is. By the multi-objective optimization, a Pareto optimal solution is obtained, which shows that an increase in exergy efficiency would increase the required heat exchange area per net power output. •LNG is employed as heat sink of a transcritical CO2 power cycle.•The effects of several parameters on system performance are examined.•A multi-objective parametric optimization is conducted by NSGA-II.